2022
DOI: 10.1177/1357633x221123409
|View full text |Cite
|
Sign up to set email alerts
|

Cancer care and management during COVID-19: A comparison of in-person, video and telephone consultations

Abstract: In Australia, the COVID-19 pandemic has resulted in the exponential growth in the delivery of telehealth services. Medicare data indicates that the majority of telehealth consultations have used the telephone, despite the known benefits of using video. The aim of this study was to understand the perceived quality and effectiveness of in-person, telephone and videoconsultations for cancer care. Data was collected via online surveys with consumers ( n = 1162) and health professionals ( n = 59), followed by semi-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 20 publications
0
8
0
Order By: Relevance
“…Despite this, telephone was most frequently used for consultations and nearly a third of consumers were not offered a video consultation. In response to COVID‐19, clinician access to video has increased rapidly 19 . Traditionally, clinicians have identified internet connectivity and poor‐quality audio and video as common barriers for consumers using telehealth 1 .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Despite this, telephone was most frequently used for consultations and nearly a third of consumers were not offered a video consultation. In response to COVID‐19, clinician access to video has increased rapidly 19 . Traditionally, clinicians have identified internet connectivity and poor‐quality audio and video as common barriers for consumers using telehealth 1 .…”
Section: Discussionmentioning
confidence: 99%
“…Using an online survey and semistructured interviews, telehealth experiences for cancer care were collected from consumers. The methods for this study have been previously published 19 …”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The study compared in-person, video, and telephone visits and reported that when compared with in-person visits, older adults were more likely to participate in telephone visits than video visits [21]. Communication was improved with video consultations, providing an increased level of quality of care compared with telephone which was found more suitable for shorter visits such as prescription refills [21,25].…”
Section: Telemedicine Modes Of Communicationmentioning
confidence: 99%